Gene Expression of Monocarboxylate Transporters and Oocyte‐secreted Factors in Bovine Cumulus‐oocyte Complexes Selected by Brilliant Cresyl Blue. Issue 5 (17th August 2015) - Lopes, EF; Marques, LS; Duranti, RG; de Oliveira, ATD; Lopes, RFF; Rodrigues, JL
Contents: Oocyte selection based on the brilliant cresyl blue (BCB) staining test has been successfully used to differentiate between competent and incompetent bovine oocytes. Here, the expression of genes involved in transport of monocarboxylates ( Mct1‐4 ) and oogenesis specific genes ( Bmp15, Gdf9 and Has2 ) in BCB+ and BCB‐ selected immature and mature bovine cumulus‐oocyte complexes (COC) was evaluated. In order to find specific molecular markers to characterize successful oocyte maturation, our study was also aimed at identifying the expression of Mcts and oogenesis specific genes in denuded oocytes and cumulus cells. Immature COCs morphological appropriate were (i) stained with 26 mm BCB for 90 min before IVM, (ii) exposed to same incubation conditions as stained COCs, but without BCB (holding group) or (iii) transferred into a maturation medium immediately after morphological selection (control group). mRNA expression was investigated by RT‐PCR in COCs before and after IVM. No relationship was observed in the relative expression of Has2, Gdf9, Bmp15 or Mct1, 2 and 4 transcripts between BCB+ and BCB− COCs. Transcripts analysis showed that Gdf9 and Bmp15 in BCB+, BCB− and holding groups were up‐regulated (p < 0.05) before IVM, while Has2 was up‐regulated (p < 0.01) after IVM in the control group. Other genes remained stable during maturation ( Mct1, 2 and 4 ). Our results showed, for the first time, Mct1, 2 and 4 expression in bovine COCs. Mct1 and Mct4 transcripts were present in denuded oocytes and cumulus cell, while Mct2 was detected only in cumulus cells. These differences between the three isoforms in localization suggest unique roles for each in monocarboxylate transport during maturation.